(untitled) (Stato, Chiese e pluralismo confessionale, 2014)
Il contributo - già apparso su Cardozo Law Review, vol. 35, october 2013, n. 1, pp. 213-265 - è ora pubblicato per la cortesia dell’Editore TABLE OF CONTENTS: Introduction - I. Legislative History A. Early Legislative History of the Information Return Requirement - The Revenue Act of 1943 - 2. The Imposition of the Unrelated Business Income Tax in 1950 - 3. Expanding the Information Return and Unrelated Business Income Tax in 1969 - B. Televangelist Scandals During the 1980s - C. Recent Legislative History of the Information Return - 1. The William Aramony Scandal and Aftermath - 2. Recent Revisions to Form -II. Increased public access to and use of FORM 990 Information Returns - III. Churches should not be exempt from filing form - A. Churches Are Especially Susceptible to Financial Abuses /- 1. Many Churches Lack Basic Forms of Oversight and Accountability, Revealing Too Much Trust in the Honesty of Religious People - 2. Churches Where Power is Concentrated in the Hands of One Leader Provide the Ideal Structure for Financial Abuse - 3. Even at Churches with More Independent Boards, Leaders Still Maintain Undue Influence - 4. The Nature of Spiritual Leadership Gives Church Pastors Extraordinary Power - 5. Hierarchical Churches also Lack Proper Financial Oversight, and Lay Members Have Little Say in Accountability - B. Churches Themselves Would Benefit from Increased Transparency and Accountability - 1. Greater Transparency May Increase Donations - 2. Requiring Transparency Would Mitigate the Inevitable Fall in Donations from Scandals at Similar Institutions -3. Financial and Other Scandals, Caused or Exacerbated by Lack of Transparency, Have the Potential to Damage the Spiritual Lives of Churchgoers - C. Many Churchgoers Would Likely Welcome More Financial Transparency - D. Financial Transparency is Consistent with the Teachings of Many Churches - E. Self-Regulation Is Insufficient to Prevent Financial Abuse - F. The Public Has a Right to Know What Happens to Taxpayer Money Funneled to Churches - IV. Constitutional Issues - A. Removing the Exemption Would Not Violate Free Exercise - B. The Current Exemption May Violate the Establishment Clause - C. Requiring Churches to File the Form 990 Would Not Be Excessively Entangling – Conclusion.